The gestures of participatory art - Bala, Sruti, 1973- (Manchester University Press, 2018)
Participation is the utopian sweet dream that has turned into a nightmare in contemporary neoliberal societies. Yet can the participatory ideal be discarded or merely replaced with another term, just because it has become disemboweled into a tool of pacification? The gestures of participatory art insists that the concept of participation must be re-imagined and shifted onto other registers. Moving from reflections on institutional critique and impact to concrete analyses of moments of unsolicited, delicate participation and refusal, the book examines a range of artistic practices from India, Sudan, Guatemala and El Salvador, the Lebanon, the Netherlands and Germany. It proposes the concept of the gesture as a way of theorising participatory art, situating it between the visual and the performing arts, as both individual and collective, both internal attitude and social habitude.